Are two consecutive negative RT-PCR results enough to rule out COVID-19? (2020)
The coronavirus disease 2019 (COVID-19) pandemic is redefining the world we live in, and scientists are struggling to find the best severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) diagnostic tool. Routine testing is currently performed using real-time reverse transcription PCR (RT-PCR) of upper or lower respiratory tract secretions. We sought to demonstrate the importance of conducting RT-PCR using deep sampling when initial upper respiratory testing is negative in cases of high index of suspicion for COVID-19. We present the case of a 47-year-old man admitted for fever and bilateral pneumonia diagnosed via chest computed tomographic scan amidst the early peak of the COVID-19 pandemic, suggesting a SARS-CoV-2 infection. Two RT-PCR results from nasopharyngeal swab samples were negative. A bronchoscopy was then performed, and RT-PCR testing on bronchoalveolar lavage samples yielded positive results, confirming the diagnosis of COVID-19 pneumonia. RT-PCR samples of the lower respiratory tract likely contain a higher virus load and thus retain a higher sensitivity for SARS-CoV-2 detection.